2008
DOI: 10.1182/blood-2008-02-137695
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination induces WT1-specific T-cell responses with potential clinical relevance

Abstract: The Wilms tumor antigen, WT1, is associated with several human cancers, including leukemia. We evaluated WT1 as an immunotherapeutic target using our proven DNA fusion vaccine design, p.DOM-peptide, encoding a minimal tumor-derived major histocompatibility complex ( IntroductionDespite major advances in chemotherapy and hematopoietic stem cell transplantation, many patients with leukemia will relapse because of reemergence of tumor. However, complete molecular remissions have been achieved by infusion of dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 54 publications
(109 reference statements)
0
47
0
Order By: Relevance
“…6,39 In these studies, the optimal configuration for the induction of CD8 þ T-cell immunity consisted of a C-terminal fusion of a minimal epitope with domain 1 of FrC (here referred to as TTFC for simplicity). 6,31,40 Here, we show for the first time that the beneficial effects of TTFC fusion do also apply to full-length gene products, thereby allowing antigen presentation via multiple HLA class I alleles. What is the mechanism by which fusion with a carrier molecule enhances DNA vaccine immunogenicity?…”
Section: Discussionmentioning
confidence: 81%
“…6,39 In these studies, the optimal configuration for the induction of CD8 þ T-cell immunity consisted of a C-terminal fusion of a minimal epitope with domain 1 of FrC (here referred to as TTFC for simplicity). 6,31,40 Here, we show for the first time that the beneficial effects of TTFC fusion do also apply to full-length gene products, thereby allowing antigen presentation via multiple HLA class I alleles. What is the mechanism by which fusion with a carrier molecule enhances DNA vaccine immunogenicity?…”
Section: Discussionmentioning
confidence: 81%
“…In pDOM-epitope DNA vaccines [55,82,83] this help is provided by the first domain of tetanus toxin which can induce CD4 + T-cell responses without subverting the tumor specificity of the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of research groups have chosen to study MHC class I binding epitopes rather than MHC class II, since the effector cells in this scenario are thought to be [55,82,83] and altered WT1 peptide ligands designed for MHC class II are also being explored [84].…”
Section: Mhc Class II Epitopesmentioning
confidence: 99%
“…This guarantees the sole expression of the HHD molecule on the cell surface, making sure that any identified CTL epitopes are HLA-A2 restricted [98]. HHD mice allow epitopes which are presented on human HLA-A2 to be examined for their ability to induce T cell responses in a variety of studies; for example STEAP, a prostate tumour antigen has been shown to be targeted by anti-tumour T cells [99] and DNA vaccines encoding Wilms tumour antigen 1 induce cytotoxic responses in mice [100] using this model system.…”
Section: Genetically Modified Micementioning
confidence: 99%